SPACE MILITARIZATION: THE US-CHINA ARMS RACE AND ITS IMPACT ON SOUTH ASIA - Muhammad Hamza Farooqi (`, 2025)
The focus of this essay is to provide a deep insight into the intensifying US-China arms race in space and its broad implications for the South Asian world from the theoretical lens of realism in IR. Both superpowers are scaling up their space armament as they fight for strategic and technological supremacy; the impact is shifting the dynamics of global security and amplifying insecurities in particular regions. South Asia, a geopolitically vulnerable region already steeped in longstanding rivalries and uncertain stability, has become further mired in the arms race of these world leaders. It uses the realist paradigm – the prioritization of power, security and state survival – to analyze the forces driving the US-China space race and how they affect South Asia’s security context. Analyzing some of the major trends, such as ASAT test firings, the development of space-based surveillance, and the geopolitical calculations of regional alliances, the study shows the existence of a regional arms build-up. It goes on to examine how these forces might re-inflame conflict and make the area unstable. These results highlight how South Asian states must respond to the twin issues of technological dependence and strategic vulnerability in a militarizing space environment in rapid flux. Keywords: Space militarization, US-China strategic competition, South Asia, realist theory, international security, arms race.